Artificial intelligence’s role in industry 4.0-driven sustainable supply chains for small and medium-sized enterprises - Fahima, Umme; Solomon Koilpillai, Charis Samuel; Hammad, Muhammad Yahya; Syed Radzi, Rahamaddulla; Sorooshian, Shahryar (Learning Gate, 2025)
This study investigates how artificial intelligence (AI) enables sustainable supply chain transformation and the institutional and organizational factors that mediate successful AI-driven green outcomes. We conducted a mixed-methods bibliometric and thematic analysis of literature on AI and green supply chains, combining bibliographic coupling and co-word analyses across 124 Scopus records and synthesizing managerial insights from representative empirical studies. Four thematic clusters emerged: (1) performance-driven green strategies; (2) enablers and barriers to green supply chains; (3) circular economy and digital transformation; and (4) technological integration and big data capabilities. Results indicate that organizational digital maturity, data governance, and cross-functional capabilities critically enable AI-driven sustainability; regulatory pressure and consumer demand alone are insufficient. AI has substantial potential to improve environmental performance and resilience when integrated with aligned strategy and internal capabilities. Managers should prioritize digital maturity, data governance, skills development, and ecosystem partnerships to scale AI-enabled sustainability while avoiding superficial greenwashing.